Trends and projections of the burden of disease for male infertility in China from 1990 to 2021: an analysis from the Global Burden of Disease 2021 study - Ran Xu; Xin-jun Wang; Qing-cheng Lin; Yan-ting Zhuang; Qing-ying Zhou; Nai-fen Xu; Ding-qin Zheng (Frontiers in Reproductive Health)
BackgroundCurrently, male infertility represents a serious disease burden worldwide, and China is one of the most affected countries. The aim of this study was to examine the evolution of the disease burden of male infertility in China during the period 1990–2021 and to project the trend for 2022–2036.MethodsBy screening and processing data from the Global Burden of Disease 2021, this study obtained data on the prevalence, disability-adjusted life years and corresponding rates and age-standardised rates of male infertility between 1990 and 2021. To assess the trend in the burden of male infertility over the past 30 years, the annual percentage change and the average annual percentage change were calculated from the above data using Joinpoint regression models. In addition, age-period-cohort models were used to estimate the independent effects of age, period and cohort factors on male infertility, and Bayesian projection models were used to predict the trend in the disease over the next 15 years.ResultIn both 1990 and 2021, the burden of male infertility tended to increase and then decrease with age, with the heaviest burden in the 35–39 age group. Meanwhile, the Joinpoint model found statistically significant average annual percentage changes in age-standardised prevalence and age-standardised disability-adjusted life years of 0.14% and 0.19%, respectively. In addition, the trend for both was a gradual increase over time until 1994 and a gradual decrease over time after 1994. In the age-period-cohort analysis model, age, period and cohort effects indicated that 35–39 years, 1997–2001 and 1945–1949 were the years with the highest risk of male infertility. Finally, the Bayesian projection model suggested that the disease burden of male infertility in China would show a decreasing trend over the next 15 years.ConclusionFrom 1990 to 2021, the disease burden of male infertility in China generally increased. However, thanks to a number of factors, including China's proactive health policies and effective management, the burden of disease has continued to decrease in the last decade and is projected to continue declining from 2022 to 2036. To sustain this positive trend, it remains essential for China to maintain and strengthen effective management and control of male infertility.